Bantuan Hukum terhadap Kaum Difabel Korban Tindak Pidana Upaya mewujudkan Acces to Justice - Anggun Malinda; Ekha Nurfitriana; M. Yasin Al Arif (Fakultas Hukum Universitas Islam Indonesia, 2014)
Legal aid and protection for disabled people are still difficult to get. Worse, there are not any legal institutions which protect them. The problems discussed in this research are: first, how is the issue of legal aid to disabled people as criminal victims and its challenges? Second, what kinds of legal aid that should be given to disabled people as criminal victims in order to bring access to justice? This was an empirical and normative legal research. The research findings show that: first, the advocacy of disabled people as the victims of violence has been handled by several LSM (Non-Governmental Organizations) in the field of legal aid. Most of the handled cases are discontinued in the middle of the process due to some issues regarding the legal aids, such as issues related to legal aid agencies, disabled victims, victims, and law enforcement apparatus. Second, the ideas suggested to legal aid agencies are to provide supervision from psychologists, translators, and special advocates to handle disabled victims. The ideas suggested to the police are to provide special investigating officers for disabled people, such as assigning police woman for rape and violence cases involving disabled woman victims; and in the judicial proceedings i.e. by one time investigation system in the investigation step in which judges review the victims’ testimony based on police investigation report in the investigation step.